Optimization of Welding Parameters and Cooling Media on the Mechanical Properties of SMAW Welding on CNP Channel Steel Material using Taguchi Method - Mubarok, Khamdi; Izzudin, Mohammad Nur; Muzakki, Hakam; Anwar, Muhammad Nurul (Universitas Trunojoyo Madura, 2023)
CNP channel steel, commonly referred to as lightweight C-channel steel, is a steel bar characterized by its 'C' shaped cross-section, produced through the cooling process of steel plates or strips. This type of steel holds significant importance in construction, as the strength of its connections plays a critical role in its load-bearing capacity. In this research, a low carbon steel, specifically CNP channel steel with a 3 mm thickness, was selected as the base material. The welding parameters included varying welding currents (70 A, 80 A, and 90 A), welding speeds (2 mm/s, 3 mm/s, and 4 mm/s), and different cooling media (NaCl solution, mineral water, and lubricant). Following the welding process, tensile tests were conducted to evaluate the mechanical properties of the welded joints. The Taguchi Orthogonal Array L9(33) method, comprising 9 experiments with 3 replications, was utilized to determine the optimal combination of parameters. The results show that the highest tensile strength recorded was 38.75 N/mm² in the combination of a welding current of 80 A, welding speed of 4 mm/s, and cooling media using mineral water. On the other hand, the lowest tensile strength recorded was 12.70 N/mm² (70 A, 3 mm/s, NaCl solution). The welded joints indicated that 16 specimens experienced brittle fractures, while 11 specimens exhibited ductile fractures. Brittle fractures mainly occurred at the welding joints, while ductile fractures were found in the base material. Based on the Taguchi method, the optimal parameter values were identified a welding current of 90 A, a welding speed of 4 mm/s, and using lubricant as the cooling media which welding current holds the highest percentage of contribution.